Effect of Doped Indium Tin Oxide on Bonding and Morphology of Monomer Cholesteryl Acrylate - Afrizal; Rahman, Arif; Hidayati, Nurul; Iwan, S. (Asian Journal of Chemistry, 2019)
Monomer cholesteryl acrylate was doped by indium tin oxide (ITO) which succeeded in becoming composites in photopolymerization process using UV curing method having various polymerization time (15, 20, 25, 30 and 35 min) at 60-70 °C. The goal of this study is to know the effect of polymerization time to characterize the conductivity properties of composite cholesteryl acrylate-ITO. All the spectra confirmed the peaks at 600-550 cm-1 which attributed the doping of ITO in the composite cholesteryl acrylate-ITO. The XRD patterns of polymer cholesteryl acrylate-ITO has nematic chiral phase at 2θ = 15-20°. Some of the peaks are appeared at 15.2734° and 16.7266°, while other peaks of indium tin oxide appeared at 30°, 50° and 60°. The surface morphology of polymer cholesteryl acrylate-ITO showed the existence of sphere. The value conductivity of polymer cholesteryl acrylate-ITO is found to be 1.8390 × 10-10 S/m.